Sustainable performance of honey and propolis production in the countryside of the State of São Paulo, Brazil - de Amorim, Fernando Rodrigues [UNESP]; Alves, Marcos Rafael; Silva, Saulo André; Pigatto, Gessuir [UNESP] (My University, 2022)
Beekeeping can be an alternative source of income for family farmers and, thereby, it can help to improve local development in a sustainable way. However, it requires specialized knowledge on technical and productive levels. In this sense, can there be an implementation of a project for the production of honey and propolis that configures a feasible alternative for sustainable rural development? This study aimed to analyze the financial, economic, and risk viability for the implementation of a project focused on beekeeping activity. The research took place in the city of Taquaritinga, in the countryside of the state of São Paulo (Brazil). This work is characterized as a case study with an exploratory approach, carried out through quantitative data from real scenarios (optimistic-10%) and pessimistic--10%), through the liquid revenue of a beekeeper. The project analysis used economic viability indicators such as: Net Present Value (NPV), Internal Rate of Return (IRR) and Payback. The financial analysis was carried out through a Cash Flow (CF), a Profitability Index (PI) and a risk analysis via Monte Carlo Simulation (MCS). The results showed that investment in beekeeping is feasible in all scenarios. In the real scenario, net revenue was US$ 1,424.00/year, Pavback 2.1/year, VPL US$ 3,810.62, and IRR 47%; in the pessimistic scenario, net income was $1,219.00, Payback 2.5/year, VPL $2,915.71, and IRR 38%, and in the optimistic scenario, net revenue was $1,628.00/year, Payback 1.9/year, VPL $4,734.26, and IRR 56%.Finally, IP was 1.19. Risk analysis mentioned a level of certainty that the probability occurs in all scenarios greater than 67%, since the results were higher than the Minimum Rate of Attractiveness (MRA).
Keywords: Cash flow; Economic viability; Investment; Risk analysis; Scenario analysis